Antibacterial dental restorative materials: A review. - Chen, L. I. A. N. G.; Suh, B. I.; Yang, J.
PURPOSE: To provide updated summary information about antibacterial dental materials, primarily covering the literature from 2012 through 2017. METHODS: A key-worded search was conducted of peer-reviewed literature (Titles/Abstracts)indexed by PubMed databases, constrained to "English" and " dental" publications between the years 2012 and 2017. Key words applied to the search included: antimicrobial, antibacterial, primer, bonding agent, adhesive, cement, composite, liner, sealant, etchant, and core-build-up. Titles and abstracts of the articles returned by the search were reviewed and evaluated for appropriateness for inclusion in this review. RESULTS: A variety of antibacterial agents have been incorporated into experimental and commercial dental restorative materials to provide antibacterial activity in dental applications. No new antibacterial compounds were introduced in this review period (2012-2017), since the last review of period of 1980-2012. Antibacterial agents include leachable compounds (e.g. benzalkonium chloride, chlorhexidine), polymerizable monomers (e.g. quaternary ammonium methacrylates), and filler particles (e.g. silver nanoparticle). During the 2012-2017 review period, many antibacterial agents were tested in experimental formulations, but only four agents (benzalkonium chloride, chlorhexidine, glutaraldehyde, and MDPB)were used in commercial products. CLINICAL SIGNIFICANCE: Leachable antibacterial agents are the most frequently used type of antibacterial dental materials, but their efficacy may be short-lived due to their characteristic burst effect. Solid filler particles appear to be effective antibacterial agents, especially given their ability to reduce biofilm formation, but the color stability of their component metal particles is unfavorable for use in a commercial product. Polymerizable antibacterial agents (MDPB)are theoretically a good choice of material because they are very effective at killing any residual bacteria in a cavity preparation prior to polymerization, however, apart from their proven effect on reduction of biofilm formation, their long-term clinical performance is still questionable.
Keywords: ANTIINFECTIVE AGENT; DENTAL MATERIAL; METAL NANOPARTICLE; SILVER; TOOTH CEMENT